The feasibility study of shear wave elastography in the diagnosis of erectile dysfunction - Da-Kun Zhang; Yun-Lin Li; Jing-Bo Guan; Zhi-Xuan Li; Min Sun (Scientific Reports)
Abstract The aim of this study was to explore the value of Shear wave elastography (SWE) in evaluating vascular and nonvascular erectile dysfunction. In this study, erectile dysfunction (ED) patients enrolled (n = 114) received SWE and Doppler ultrasonography (PCDU) exams. The peak systolic velocity (PSV) and end-diastolic velocity (EDV) were used as the classification standard. The performance of the SWE was assessed with the receiver operating characteristic curve, sensitivity and specificity. The rigidity alterations of corpus cavernosum penis with age was also investigated. SWE values of corpus cavernosum penis (CCP) before intracavernosal injection (ICI) negatively correlated with age of patients in vascular ED group (r = -0.288, P < 0.05). In erectile or flaccid state, the SWE value of vascular ED was significantly larger than non-vascular ED. When the cut-off value for SWE values of CCP 0.88 m/s in erectile state and 2.32 m/s in flaccid state, the areas under the receiver operating characteristic (ROC) curve were 0.700 (sensitivity: 77.78%, specificity: 60.00%) and 0.612(sensitivity: 68.52%, specificity: 51.67%) in erectile or flaccid state, respectively. This study provides preliminary evidence that SWE in flaccid state could be non-invasive methods used to moderate predict vascular ED.